Multi-wavelength source based on SOA and loop mirror - Ahmad, Harith; Shahabuddin, Nurul Shahrizan; Harun, Sulaiman Wadi (INOE, 2009)
A multi-wavelength fiber ring laser is demonstrated using a semiconductor optical amplifier (SOA) and a Sagnac loop mirror. The output spectrum of the proposed laser is quite stable at room temperature and the output power can be adjusted by controlling the bias current of the SOA. At bias current of 150 mA, 6 lines are obtained with an output power of at least - 40 dBm, signal to noise ratio of 25 dB and channel spacing of 1.49 nm. The number of lines is determined by the length of polarization maintaining fiber used in the Sagnac loop mirror. There is no need of optical pump lasers for this multi-wavelength source.